CubeSat's attitude determination using GNSS antenna array - Allahvirdizadeh, Amir; El-Mowafy, Ahmed (2022)
The attitude information of a CubeSat is essential to keeping the satellite in its favourable orientations in the mission and sensor positioning using precise orbit determination. The attitude of CubeSats can be determined using sun sensors, magnetometers, and star trackers. However, these sensors have some issues, including unavailability in shadow for sun sensors, low accuracy for magnetometers, and additional costs for star trackers. In this study, we propose an alternative method for the CubeSats attitude determination using the GNSS observations of an antenna array. Fixing the estimated double-differenced ambiguities as integer values equips the model with precise phase observations. In addition, the known geometry of the antenna array in the CubeSats reference frame helps us apply the rotation matrix's orthonormality constraints between the estimated baselines and the known ones. To validate the model, the actual observations of a 3U CubeSat from the Spire constellation are used to determine its precise orbit. An array of 3 coplanar antennae is then simulated using the definition of CubeSat's reference frame, the available quaternions from the star tracker and the precise orbits of CubeSats and GNSS satellites. The results validate the proposed method by providing acceptable Yaw, Pitch and Roll angles. The proposed model has the advantage of applying to the single-frequency receiver onboard the 1U low-cost and low-power CubeSats.